2018
DOI: 10.1111/apt.14968
|View full text |Cite
|
Sign up to set email alerts
|

Inequity of care provision and outcome disparity in autoimmune hepatitis in the United Kingdom

Abstract: There are significant discrepancies in the care received by patients with autoimmune hepatitis in the UK. A high proportion remains on corticosteroids and there is significant treatment variability. Patients receiving care in transplant centres were more likely to achieve and maintain remission. Overall poor remission rates suggest that there are significant unmet therapeutic needs for patients with autoimmune hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…The strengths of this study are its multicentre, real‐world design and cohort size, as it is the second largest study to date to report on the outcomes of second‐line therapies in AIH patients. Real‐world studies such as this and the recent study by Dyson et al from the UK, provide important insights into the management of AIH across a wide spectrum of hospitals, and in particular the treatment options and results when standard therapy fails; a point highlighted in a recent editorial by Hupa‐Breier et al While most AIH subjects tolerate first‐line treatment well, and achieve remission, for the 20% who do not, it is important to better understand the factors that influence the effectiveness of second‐line therapies in order to optimise treatment choice and facilitate patient counselling and expectations. Our study has shown that only 60% of patients receiving MMF as second‐line therapy achieve complete remission, highlighting the importance of identifying the best candidates and looking at possible other agents such as calcineurin inhibitors where necessary.…”
Section: Discussionmentioning
confidence: 94%
“…The strengths of this study are its multicentre, real‐world design and cohort size, as it is the second largest study to date to report on the outcomes of second‐line therapies in AIH patients. Real‐world studies such as this and the recent study by Dyson et al from the UK, provide important insights into the management of AIH across a wide spectrum of hospitals, and in particular the treatment options and results when standard therapy fails; a point highlighted in a recent editorial by Hupa‐Breier et al While most AIH subjects tolerate first‐line treatment well, and achieve remission, for the 20% who do not, it is important to better understand the factors that influence the effectiveness of second‐line therapies in order to optimise treatment choice and facilitate patient counselling and expectations. Our study has shown that only 60% of patients receiving MMF as second‐line therapy achieve complete remission, highlighting the importance of identifying the best candidates and looking at possible other agents such as calcineurin inhibitors where necessary.…”
Section: Discussionmentioning
confidence: 94%
“…Short‐term side effects of steroids are well recognised. In a multicentre study by the UK‐AIH consortium, 55% patients were taking “long‐term” corticosteroids (at least 12 months after diagnosis of AIH) . Long‐term consequences of steroid therapy are not well documented in patients with AIH…”
Section: Review Criteriamentioning
confidence: 99%
“…[11][12][13][14] Notwithstanding this high initial remission rate, long-term management of AIH remains suboptimal. Despite treatment, de novo cirrhosis develops in 18 (median (range))% patients [15][16][17][18][19][20][21][22][23] and also premature death with standardised mortality ratios of 2.0-4.0. 1,15,24,25 In part, this is because AIH frequently relapses after stopping treatment and sometimes despite continuing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, management of AIH differs significantly even among expert centers . Therefore, the study by Dyson et al, published in a recent issue is an important contribution to gain further insight into real‐world management of AIH in particular since the study provides data not only from large academic centers . Interestingly, the reported remission rates in this study are lower than those reported in several publications.…”
mentioning
confidence: 51%